The Pervious Concrete and Pervious Mortar as Water Filter in Decentralized Water Treatment– a Review - Yogafanny, Ekha; Triatmadja, Radianta; Nurrochmad, Fatchan; Supraba, Intan (UIR PRESS, 2024)
Decentralized water treatment system is water treatment carried out by the community on a household-scale. One of the technologies that have been developed to gain freshwater is the pervious concrete filter (PCF). This study aims to provide the researchers with an understanding of the pervious concrete filter as a potential filter technology in water treatment. The method used is a literature review from several papers and reports related to pervious concrete from past to present. PCF is a filter made from a mixture of aggregate, cement, and water with a specific ratio. PCF has enough water and air permeability due to interconnected macro pores. Some properties such as porosity, permeability, and pores size determine the ability of PCF to remove the contaminants in the water. These properties were controlled mostly by the aggregate size, aggregate-cement ratio, water-cement ratio, etc. According to its characteristic, the PCF shows a prospect to be used as water filter mainly in a decentralized water treatment system. Besides, the understanding of PCF is a basis to develop a pervious mortar filter that slightly different in the aggregate sizes used in this composite.